1889 N.C. Sess. Laws 820 - (:unkn) unknown (My University, 1889)
Ch. 178, § 3: That it shall be a misdemeanor for any person to . . . fire off a gun or pistol in hearing distance of those assembled for or occupied in divine worship at said church.
Keywords: DISCHARGE